PENGARUH EKSTRAK AKAR ENCOK TERHADAP PERTUMBUHAN STAPHYLOCOCCUS AUREUS - igede sudarmanto (Meditory : The Journal of Medical Laboratory, 2016)
Background: Resistance is defined as growth inhibition of bacteria with antibiotics. Staphylococcus aureus bacteria is known to be resistant to gentamicin and methicillin. Staphylococcus aureus can cause various infection of the skin, injuries, and system. Methods: This research is true-experimental with Posttest-Only Control Group Design and using Kirby-Bauer method by means of five concentration (20, 40, 60, 80, dan 100%). The negative control uses sterile distilled water, and the positive control uses Vancomycin 30 µg. Result: This research showed the mean of inhibition zone diameter of each concentration consecutively 16 mm, 20 mm, 22 mm, 23 mm, and 23 mm. Oneway ANOVA statistic analysis showed that the value of p is 0,000 that mean there is an influence of encok roots extract to Staphylococcus aureus growth. Conclusion: There is an influence of encok roots extract to Staphylococcus aureus growth. Seen from its ability to inhibit the growth of Staphylococcus aureus.